Influences of exocrine pancreatic insufficiency on nutrient digestibility, growth parameters as well as anatomical and histological morphology of the intestine in a juvenile pig model - Schubert, Dana Carina; Mößeler, Anne; Ahlfänger, Bianca; Langeheine, Marion; Brehm, Ralph; Visscher, Christian; Abd El-Wahab, Amr; Kamphues, Josef (Frontiers in Medicine, 2022)
In a pig model, pancreatic duct ligation (PL) leads to a complete loss of exocrine function, causing an exocrine pancreatic insufficiency (EPI) without affecting endocrine function, allowing research of clinical effects and therapy options. This study aimed to investigate effects of experimentally induced EPI in juvenile pigs on digestion and intestinal morphology. Eight female juvenile cross-bred pigs (BW 54.8 kg at the start of the study) were included. Three animals were considered as a control (CON group), and in five animals the ductus pancreaticus accessorius was ligated (PL group). During the ten-week trial period, body weight and body measurements were recorded regularly. At the end of the trial, gastrointestinal tract (GIT) was investigated macroscopically and histologically and weight and digesta samples of individual segments were obtained. The pigs in the CON showed a significantly higher apparent total tract digestibility of crude protein and crude fat (87.8 and 79.9%, respectively) compared to PL (52.4 and 16.6%, respectively). Significant differences were noted in relative weights of duodenum, jejunum and colon (with and without digesta) and also in absolute weights of jejunum and colon. The mean number of nuclei in the transverse section in stratum circulare were significantly higher in all intestinal segments in CON compared to PL. Overall, EPI results in reduced growth rate and impaired nutrient digestibility.